2022
DOI: 10.1101/2022.01.07.475305
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A Saturated Map of Common Genetic Variants Associated with Human Height from 5.4 Million Individuals of Diverse Ancestries

Abstract: Common SNPs are predicted to collectively explain 40-50% of phenotypic variation in human height, but identifying the specific variants and associated regions requires huge sample sizes. Here we show, using GWAS data from 5.4 million individuals of diverse ancestries, that 12,111 independent SNPs that are significantly associated with height account for nearly all of the common SNP-based heritability. These SNPs are clustered within 7,209 non-overlapping genomic segments with a median size of ~90 kb, covering … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(31 citation statements)
references
References 37 publications
2
29
0
Order By: Relevance
“…Given the relatively short time since admixture in African Americans (approximately 8 generations), we expect that regions of European ancestry in modern-day African Americans feature the same LD structure as the European source population contributing to the admixture event 24 . Moreover, others have previously demonstrated that there is low Fst and high correlation of allele frequencies between various European populations 3436 . Empirically, we also find that nearly all (95%) SNPs that are tightly linked ( r 2 > 0.8) in European Americans in MESA are also tightly linked in regions of European ancestry in African Americans in MESA.…”
Section: Resultsmentioning
confidence: 95%
“…Given the relatively short time since admixture in African Americans (approximately 8 generations), we expect that regions of European ancestry in modern-day African Americans feature the same LD structure as the European source population contributing to the admixture event 24 . Moreover, others have previously demonstrated that there is low Fst and high correlation of allele frequencies between various European populations 3436 . Empirically, we also find that nearly all (95%) SNPs that are tightly linked ( r 2 > 0.8) in European Americans in MESA are also tightly linked in regions of European ancestry in African Americans in MESA.…”
Section: Resultsmentioning
confidence: 95%
“…A concerted effort is underway to address this historical imbalance and develop new methods, such as multi-ancestry meta-analysis (MAMA) (Turley et al, 2021a), that improve genetic prediction for other ancestry groups by utilizing European-ancestry GWAS results in combination with LD structures across populations. Furthermore, GWASs of non-European samples are increasingly being conducted (Yengo et al, 2022), which will also improve the predictive power of PGIs for and the generalizibility of findings for those ancestry groups.…”
Section: Discussionmentioning
confidence: 99%
“…At the time of writing, the biggest sample size of a GWAS is 5.4 million(Yengo et al, 2022).5 Population stratification is a form of confounding where the genetic makeup of ancestors influences one's genetic makeup as well as an outcome through nongenetic pathways. More specifically, if a population is stratified into subpopulations that do not mate randomly and an outcome happens to be more common in one subpopulation for nongenetic reasons, then the outcome will appear to be correlated with any SNPs that also happen to be more common in that subpopulation.…”
mentioning
confidence: 99%
“…However, complex traits, such as body size, are likely affected by many genes. For example, recent studies of human genetic variation using data from 5.4 million individuals report finding over 12,000 independent loci associated with height (Yengo et al 2022). In the laboratory strain of C. elegans, we know many loci that quantitatively affect body size and shape.…”
Section: Candidate Genes For Variation In Body Sizementioning
confidence: 99%